2018
DOI: 10.1016/j.cocom.2018.e00330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of orientation and mode of loading on deformation behaviour of Cu nanowires

Abstract: Molecular dynamics simulations have been performed to understand the variations in deformation mechanisms of Cu nanowires as a function of orientation and loading mode (tension or compression). Cu nanowires of different crystallographic orientations distributed uniformly on the standard stereographic triangle have been considered under tensile and compressive loading. The simulation results indicate that under compressive loading, the orientations close to <100> corner deform by twinning mechanism, while the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
3
13
1
Order By: Relevance
“…It can be seen that the yield stress asymmetry for twinned nanopillars is different from that of the perfect nanopillars (higher the number of twin boundaries, lower the asymmetry), which indicates that the twin boundaries can also influence the tension-compression asymmetry. Previous studies have shown that the asymmetry in yield stress arises due to different values of Schmid factor for leading partials under tensile and compressive loading [29]. Further, Salehinia and Bahr [30] have shown that the asymmetry in the strength of nanowires decreases with increasing defect density, which is in agreement with the present findings.…”
Section: Effect Of Twin Boundaries On Stress-strain Behaviour and Yiesupporting
confidence: 92%
See 1 more Smart Citation
“…It can be seen that the yield stress asymmetry for twinned nanopillars is different from that of the perfect nanopillars (higher the number of twin boundaries, lower the asymmetry), which indicates that the twin boundaries can also influence the tension-compression asymmetry. Previous studies have shown that the asymmetry in yield stress arises due to different values of Schmid factor for leading partials under tensile and compressive loading [29]. Further, Salehinia and Bahr [30] have shown that the asymmetry in the strength of nanowires decreases with increasing defect density, which is in agreement with the present findings.…”
Section: Effect Of Twin Boundaries On Stress-strain Behaviour and Yiesupporting
confidence: 92%
“…With increasing strain, the extended dislocations belonging to different slip systems interact and results in the formation of a stacking fault tetrahedron (Figure 5b). The nucleation of trailing partials under compressive loading is favoured due to its high Schmid factor value as compared to leading partial [29]. Different from compressive loading, the deformation under tensile loading of perfect <112> Cu nanopillars occurs through the slip of Shockley partial dislocations ( Figure 5(c-d)).…”
Section: Deformation Mechanisms In Perfect <112> Cu Nanopillarsmentioning
confidence: 99%
“…This condition is readily met in <100> nanopillar deforming under compression, <110> and <111> nanopillars under tension. As a result, numerous studies have reported twinning in these orientations and loading conditions [2,8,9,10]. Further, when twinning occurs on limited twin systems, nanopillars undergo complete reorientation [10,11], which also leads to sequential reorientation [12], shape memory and pseudo-elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, numerous studies have reported twinning in these orientations and loading conditions [2,8,9,10]. Further, when twinning occurs on limited twin systems, nanopillars undergo complete reorientation [10,11], which also leads to sequential reorientation [12], shape memory and pseudo-elasticity. However, when twinning occurs on multiple twin systems, it is possible that the twins belonging to different twin systems interact and form a more complex twin-twin junctions.…”
Section: Introductionmentioning
confidence: 99%
“…In nanopillars/nanowires, the surface mediated plasticity has been identified as a dominant deformation mechanism [2,3,4], while in bulk materials dislocation multiplication, pile-up, cross-slip and other forest mechanisms are known to play the dominant role. The yielding in FCC nanopillars occurs through the nucleation of Shockley partials or extended dislocations from the surface and it can be influenced by a variety of factors like nanowire size, shape, orientation, temperature and strain rate [1,3,5,6,7,8]. As a result, the yield strength of the nanopillars is also sensitive to all these factors.…”
Section: Introductionmentioning
confidence: 99%